Xyloglucan endotransglucosylase/hydrolase 25 positively regulates the lead tolerance in Raphanus sativus - Han, Tong; Cui, Yongmei; Jing, Yang; Liu, Meiying; Chen, Xuanchao; Song, Yinghui; Gu, Xinping; Wang, Jiahao; Wang, Long (Frontiers in Plant Science, 2025)
Raphanus sativus, an important root vegetable native to China, is widely cultivated for its nutritional value and diverse applications. However, it is highly sensitive to lead (Pb) stress, with Pb predominantly accumulating in the roots. Previous studies have highlighted the pivotal role of xyloglucan endotransglucosylase/hydrolase (XTH) in plant responses to heavy metal stress. Despite this, a comprehensive identification, molecular characterization, and functional analysis of the XTH gene family in R. sativus has been lacking. In this study, 28 XTH genes were identified in R. sativus. Gene structure analysis revealed the presence of eight conserved motifs, along with variations in exon-intron organization and chromosomal distribution across all chromosomes. Phylogenetic analysis of XTH genes from R. sativus, Arabidopsis thaliana and Oryza sativa grouped them into five distinct clades, suggesting their evolutionary conservation and potential functional diversification. Transcriptome sequencing and qRT-PCR analysis showed that RsXTH25 was strongly induced by Pb stress. Transgenic hairy roots overexpressing RsXTH25 exhibited enhanced Pb tolerance, evidenced by reduced chlorosis, increased fresh weight, improved photosynthetic performance, and lower oxidative damage under Pb stress. Furthermore, several transcription factors, such as RsERF2, RsHD-ZIP22, and etc., exhibited strong positive correlations with RsXTH25, implying their roles in regulating Pb-induced RsXTH25 expression. Overall, this study provides insights into the XTH gene family in R. sativus and highlights their critical roles in Pb stress response.